1980
DOI: 10.1007/bf00237796
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of a goal-directed movement in the monkey

Abstract: The participation of the dentate nucleus (DN) in the initiation of a voluntary movement was investigated in five baboons (Papio papio). In these experiments, we have analyzed the effects of excluding the DN on the latency (reaction time, RT) of a learned goal-directed movement. Two techniques were for excluding the DN. In three animals, the structure was cooled with a probe, stereotaxically implanted on the side ipsilateral to the active hand. In two others, a partial electrolytic destruction of the DN ipsilat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1984
1984
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…The magnitude of the increase in reaction time was not significantly different for ThumbϩIndex than for Thumb or Index tasks. This finding agrees with most studies of simple movements which have reported an increase in reaction time following inactivation of the dentate nucleus (MeyerLohmann et al 1977;Mink and Thach 1991;Thach et al 1992;Trouche and Beaubaton 1980). There was no observed weakness after inactivation.…”
Section: Deficits In the Performance Of The Constrained Digit Taskssupporting
confidence: 92%
“…The magnitude of the increase in reaction time was not significantly different for ThumbϩIndex than for Thumb or Index tasks. This finding agrees with most studies of simple movements which have reported an increase in reaction time following inactivation of the dentate nucleus (MeyerLohmann et al 1977;Mink and Thach 1991;Thach et al 1992;Trouche and Beaubaton 1980). There was no observed weakness after inactivation.…”
Section: Deficits In the Performance Of The Constrained Digit Taskssupporting
confidence: 92%
“…Many of these signs are characterised by problems in movement timing. For instance, cerebellar patients often take longer to initiate a movement in response to a specific stimulus (Holmes 1917;Beppu et al 1984;Inhoff et al 1989), an observation confirmed by cerebellar lesion studies in nonhuman primates (Meyer-Lohmann et al 1977;Lamarre et al 1978;Trouche and Beaubaton 1980;Chapman et al 1986). In addition to delayed reaction times, it has been recently shown that patients with cerebellar lesions are unable to generate smooth, temporally symmetric movement profiles (Brown et al 1990).…”
Section: Movement Onset Times Associated With Cerebellar Dysfunctionmentioning
confidence: 91%
“…In contrast to the motor cortex, there remains considerable debate on whether the cerebellum specifically codes parameters of a movement such as direction or amplitude (Trouche and Beaubaton, 1980; Mink and Thach, 1991; Thach et al, 1992; Horne and Butler, 1995; Ebner et al, 2011). Neural changes in movement-related activity in cerebellar nuclei are generally thought to coordinate movements across multiple joints, have a role as a temporal pattern generator, code proprioceptive information and error signalling to optimize movements and motor learning possibly through feed-forward and/or adaptive filter models, but do not specifically control initiation of movements (Sieb, 1989; Thach et al, 1992; Horne and Butler, 1995; Braitenberg et al, 1997; Ohyama et al, 2003; Jacobson et al, 2008; Dean et al, 2010; D’Angelo et al, 2011; Ebner et al, 2011).…”
Section: The Motor Thalamusmentioning
confidence: 99%